(untitled) - Pierce, John R. (Hoboken, NJ, 2005)
Major Walter Reed, writing to his wife, New Year's Eve, 1900 As he wrote to his wife of his stunning success in the mission to identify the cause of yellow fever and find a way to eradicate the disease, Walter Reed had answered the prayers of millions. For more than 250 years, the yellow jack had ravaged the Americas, bringing death to millions and striking panic in entire populations. The very mention of its presence in a city or town produced instant chaos as thousands fled in terror, leaving the frail, the weak, and the ill to fend for themselves. Yellow Jack tracks the history of this deadly scourge from its earliest appearance in the Caribbean 350 years ago, telling the compelling story of a few extraordinarily brave souls who struggled to understand and eradicate yellow fever. Risking everything for the cause of science and humanity, Reed and his teammates on the U.S. Army Yellow Fever Board invaded the heart of enemy territory in Cuba to pursue the disease-and made one of the twentieth century's greatest medical discoveries. This thrilling adventure tells the timeless tale of their courage, ingenuity, and triumph in the face of adversity.
Keywords: Yellow fever,Bệnh sốt vàng; History,Lịch sử